Development and validation of GCHSmethod used for trace level determination of carcinogenic Epichlorohydrin impurity in Rivaroxaban - Tabrez, Dr. Shaikh; Gosar, Dr. Amit; Mahadik, Neelam; Pawar, Sanjay (Asian Journal of Pharmaceutical Research and Development, 2022)
A simple, sensitive, and selective Headspace-Gas chromatography (GCHS) method was developed and validated for the trace level determination of Epichlorohydrin, which is a probable carcinogenic compound and may be present as a process impurity in Rivaroxaban drug substances. Identification and separation of analytes were achieved on a DB-Wax column having dimensions of 30 m in length and a 0.53 mm internal diameter with a 1.0 μm stationary film thickness. Nitrogen is used as a carrier gas with of flow rate of 6.0 mL/min. The run time of the method is 25 minutes. The gradient column oven-temperature programming method was used for analyte elution. The developed method was validated using ICH guidelines and found a linear in the range between 9.64 ppm and 80.31 ppm. The correlation coefficient and y-intercept observed for the linearity curve are 0.9993 and 1.75%, respectively. The limit of detection and quantitation were 3.03 ppm and 9.19 ppm, respectively. Recovery was observed for Epichlorohydrin between 94.66 % and 99.22 %. The RSD for system precision, precision at LOQ, and repeatability was less than 5.0 %. The developed method can be successfully applied to determine Epichlorohydrin in Rivaroxaban drug substances up to a very low trace level concentration. The method was found to be specific, selective, linear, precise, and accurate.